Phantom and big-fish-little-pond-effects on academic self-concept and academic achievement: Evidence from English early primary schools. (February 2021) - Televantou, Ioulia; Marsh, Herbert W.; Dicke, Theresa; Nicolaides, Christos
Abstract: The Big-Fish-Little-Pond Effect (BFLPE) suggests that school-average achievement has a negative effect on academic self-concept (ASC); some research has also verified a negative effect on students' academic achievement. Our study evaluates the compositional effects of school-average achievement on both outcomes, using a longitudinal sample of English early primary school students in Year 1 and Year 4. We provide evidence for BFLPEs in children as young as six to nine years of age. Further, we show that the BFLPE is a potential mechanism in the negative compositional effect of school average achievement in Year 1 on students' achievement in Year 4. Once adjustments for measurement error are made, the negative effect of school-average achievement on students' self-concept, and on their subsequent achievement, becomes even more negative. Our findings question previous research suggesting that attending a school with higher average achievement necessarily advances students' outcomes. Highlights: The Big-Fish-Little-Pond-Effect is verified for English students between 6 and 9 years old. No evidence for a positive school compositional effect on subsequent achievement (i.e. a peer spillover effect) is detected. Corrections for bias due to measurement error lead to both the effect of school-average achievement on subsequent achievement and academic self-concept becoming more negative. Evidence for academic self-conceptmediating the negative school compositional effect of average achievement on subsequent achievement is detected.